Ultra Sonic Technique For The Measurement Of Pressure Below Atmospheric Pressure. - Rehman, Prof. M.; Bashier, Eisa; Sidek, Dr. Othman (2004)

(untitled)
This paper deals with the theory, fabrication and test results of an ultrasonic technique which is used to measure vacuum in a container.